Decline in the Half‐Pounder Life History among Trinity River, California, Steelhead. Issue 6 (6th October 2017) - Peterson, Matthew L.; Hankin, David G.; Manishin, Kaitlyn
Abstract: Steelhead Oncorhynchus mykiss exhibit substantial life history variation throughout their range, but the "half‐pounder" life history is limited to several rivers in northern California and southern Oregon. Half‐pounders first return to freshwater as immature fish after spending just 3–5 months at sea and support valuable freshwater fisheries. In the main‐stem Klamath and Rogue rivers, historically and at present, half‐pounder expression rates were and remain high for fall‐run steelhead. We used visual classifications of the half‐pounder life history from scales collected from the Trinity River to estimate half‐pounder expression rates and investigate the role of size and age prior to ocean entry on the probability that adult steelhead expressed the half‐pounder life history. Half‐pounder expression rates among both wild and hatchery steelhead in the Trinity River have substantially declined since 1982. Among the most common age‐2 wild smolt type, 71% of adults returning in 1982 had previously made a half‐pounder run, whereas estimated rates for adults returning in various years from 1994 to 2013 averaged just 10% (range = 2–25%). Estimated returns of half‐pounders and adults from Trinity River Hatchery releases made prior to 1982 are consistent with a historically high half‐pounder expression rate. Among age‐1 hatchery steelhead smolts, a similar decline seems evident and seems in part related to a large increase in size at release in 1992. Strong negative associations were found between the size prior to ocean entry (wild and hatchery fish) and smolt age (wild fish) and the probability that an individual steelhead expressed the half‐pounder trait; smaller‐sized and younger smolts were more likely to express the trait. Further research focusing on the heritability of this life history trait should be conducted to develop strategies intended to prevent further loss of this unique life history among Trinity River fall‐run steelhead.